Dampak Resesi 2023 terhadap Harga Saham di Indonesia - Sintia Nur Afifah; Nurul Fauziyyah (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2023)
A recession is a sluggishness, as if it had stopped, in trade, industrial and so on or a decline of trade (industry) activities. The economic recession greatly affected the Jakarta Composite Index (IHSG). The phenomenon of the reddening of the stock market started after the WHO announced COVID-19 and has experienced a drastic decline since the economic recession. The economic recession that previously occurred in 1997 is expected to occur again in 2023 so that this has become the cause of negative turmoil on the global stock market, especially Indonesia. Therefore, this study aims to provide an overview of the impact of the 2023 recession on stock prices on the Indonesian capital market JCI. This research is a literacy study using previous studies related to the decline in stock prices in Indonesia, the latest information from relevant sources, and various reports on the topic being researched. The data analysis method in this study is a descriptive analysis method. The results of this study stated that the recession had a negative impact on the development of stock performance as seen from the JCI in the second week of January 2023 which was caused by economic instability, slowing company profit growth, and investor concerns.